Հայրենասիրական արձակի լեզուաոճական առանձնայատկութիւններ (հայր եւ որդի Դեւրիկեանների օրինակով) - Երկանեան, Աննա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В данной статье рассматриваются лингвостилистические особенности и библейские выражения в патриотических произведениях одного из самобытных представителей нового периода армянской прозы XX века Геворга Деврикяна и его сына Вардана Деврикяна. Подчеркивается связь произведений Геворга Деврикяна и Вардана Деврикяна с древнеармянским (грабаром) и среднеармянским языком. В статье рассматриваются стилистические особенности исторического романа, цитаты на древнеармянском и выражения на среднеармянском языках. Из средств художественной выразительности исследуются аллегория и пейзаж, подчеркивается значение характерных для Средневековья отсылок к Библии. В статье анализируются также характерное для произведений Г. Деврикяна богатство лексики, уместное использование многих древнеармянских слов и грамматических форм, среднеармянских пластов лексики, широкое применение средств языковой выразительности. Предметом рассмотрения является также книга сына Геворга Деврикяна Вардана Деврикяна «Вардананк и армянская молодежь». Подчеркивается сходство и неповторимость пера отца и сына Деврикянов. The paper examines the linguistic and stylistic features and biblical expressions in the patriotic works by Gevorg Devrikyan, one of the outstanding representatives of the new period of 20th-century Armenian prose, as well as his son Vardan Devrikyan. The connection of the works by Gevorg Devrikyan and Vardan Devrikyan with the Ancient Armenian (Grabar) and Middle Armenian languages is emphasized. The paper touches upon the stylistic features of the historical novel, the quotes in Ancient Armenian and expressions in Middle Armenian. Allegory and landscape are studied as means of literary expression, and the significance of references to the Bible, typical of the Middle Ages, is emphasized here. The paper also studies the characteristic richness of vocabulary in G. Devrikyan’s works, the appropriate use of numerous Ancient Armenian words and grammatical forms, layers of Middle Armenian vocabulary and the abundant use of linguistic expressive means. The significant book by Gevorg Devrikyan’s son Vardan Devrikyan “Vardanank and the Armenian Youth” is also a subject of consideration in this paper. The similarity and uniqueness of writing styles of father and son Devrikyan are emphasized.
Keywords: Հաղորդումներ; Բանասիրութիւն